2005
DOI: 10.2337/diabetes.54.1.212
|View full text |Cite
|
Sign up to set email alerts
|

Nitrergic Neurodegeneration in Cerebral Arteries of Streptozotocin-Induced Diabetic Rats

Abstract: Although autonomic neuropathy is recognized as an independent risk factor for stroke in diabetes, the mechanism by which autonomic nerves are involved in this pathology is unknown. Parasympathetic (cholinergic) nerves of the autonomic nervous system are known to innervate and to cause relaxation of cerebral arteries by releasing nitric oxide (NO); hence, they are called nitrergic nerves. However, the effect of diabetes on nitrergic nerves is unknown. Here, we show that perivascular nitrergic nerves around the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…However, this is the first study to show that the reduced dilator response of the cerebral arteries of ZO rats to acetylcholine is correlated with a lower expression of nNOS. Our results are supported by Cellek et al (12) who have previously shown that nNOSexpressing perivascular neurons around the basilar artery are progressively degenerated in streptozotocin-induced diabetic rats. While nNOS is normally localized to perivascular nerves associated with cerebral arteries and has several well-defined effects on cerebral vascular tone (11,13,29,38), nNOS has been shown to compensate for reduced NO and thereby restore normal NO-dependent dilation in eNOS knockout mice (36,37).…”
Section: Discussionsupporting
confidence: 91%
“…However, this is the first study to show that the reduced dilator response of the cerebral arteries of ZO rats to acetylcholine is correlated with a lower expression of nNOS. Our results are supported by Cellek et al (12) who have previously shown that nNOSexpressing perivascular neurons around the basilar artery are progressively degenerated in streptozotocin-induced diabetic rats. While nNOS is normally localized to perivascular nerves associated with cerebral arteries and has several well-defined effects on cerebral vascular tone (11,13,29,38), nNOS has been shown to compensate for reduced NO and thereby restore normal NO-dependent dilation in eNOS knockout mice (36,37).…”
Section: Discussionsupporting
confidence: 91%
“…Deficit in NO production may also be due to nitrergic neurodegeneration which was recently described by Cellek et al [10][11][12] . These authors showed that perivascular nerves degenerate in two phases in STZ-induced diabetes.…”
Section: Nos-related Systemsmentioning
confidence: 87%
“…Increased nNOS protein and NO production coincide with accumulation of advanced glycation end-products (AGEs) in the blood and tissues. Synergistic action of AGEs and endogenous NO leads to increased oxidative stress within the cell bodies, resulting in apoptosis [10][11][12] .…”
Section: Nos-related Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found a decreased response of cerebrovascular blood flow to NO synthase inhibition in diabetic patients compared with nondiabetic patients, although not enough patients were enrolled to determine significance (98). In addition, parasympathetic neurons that secrete NO into the perivascular space have been documented to degenerate and eventually die in the absence of insulin signaling (99). Numerous studies have found that HMGCoA reductase inhibitors (statins), which upregulate NO synthesis in addition to their activity in stabilizing atherosclerotic plaques (100), significantly reduce the risk of stroke (56,67,101-104).…”
Section: Endothelial Dysfunction and Nitricmentioning
confidence: 99%